Lessons from insiders: Embracing subjectivity as objectivity in victimology - Marcoux Rouleau, Alexis (International review of victimology, 2024)
Due to the prevalence of victimization in society, it is likely that many victimologists have been victimized or will be in their lifetimes. This poses a challenge for the field of victimology as traditional, positivist conceptions of ‘good science’ require researchers to be outsiders relative to populations they study. This paper asks: What are the epistemological and practical implications of victimological research conducted by researchers who have firsthand experiences of victimization? What lessons can be retained by other victimologists and researchers in general? How can these epistemological considerations be applied in practice? To answer these questions, I examine the meanings of insider and outsider status and the implications for objectivity and subjectivity as per positivist and standpoint epistemologies. I present the case of victimologists who have been victimized as well as the advantages and disadvantages of this form of insider research. I deconstruct insider–outsider, subjectivity–objectivity dualisms as they pertain to victimologists, concluding that all victimologists can be subjective whether they are technically insiders or not. In closing, I discuss how all victimologists can embrace their own and their participants’ subjectivity as a resource for objectivity by examining location, emotions and bodies, and ethics throughout the research process.